Hydrodynamic simulations of the SS 433-W50 complex - Goodall, P; Bibi, F; Blundell, K (2008)
The compelling evidence for a connection between SS 433 and W50 has provoked much imagination for decades. There are still many unanswered questions: What was the nature of the progenitor of the compact object in SS 433? What causes the evident re-collimation in SS 433's jets? How recent is SS 433's current precession state? What mass and energy contributions from a possible supernova explosion are required to produce W50? Here we comment on two of our 53 models: (i) featuring the SNR evolution alone, and (ii) the SNR combined with a simple jet model. © Copyright owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence.